A test method for manufacturing effect assessment in HCF. Issue 1 (February 2021) - Beghini, M; Bertini, L; Macoretta, G; Monelli, B D; Arcioni, M; Bagattini, A; Grilli, M; Tognarelli, L
Abstract: Surface conditions produced by manufacturing processes are known to significantly affect the fatigue strength of metallic materials. However, fatigue tests on planar specimens usually present the onset of fatigue crack in a specimen edge, where the superposition of different machining techniques and subsequent machining operations can hide the effects of the studied process. This study deals with the design of a fatigue test able to reliably assess the effects on the high cycle fatigue strength of any machining process used to produce planar surfaces. It was devised a test configuration where the specimen geometry and the loading conditions are aimed to locate the crack nucleation in the middle of the surface machined by the investigated process. This condition is achieved by employing a notched specimen and a three-point bending test configuration, where the position and geometry of the notches are designed to relieve the specimen's edges. Nevertheless, in the critical region, the stress state is quite uniaxial and uniform in the longitudinal direction. The specimen is manufactured by using the same parameters and processes adopted for full-scale components, thus producing a surface with the same properties as the real component. The designed test configuration was validated in a high cycle fatigue test aimed to compare the effects of broaching and wire electrical discharge machining on the Wöhler curve (S-N curve). The specimen geometry was tailored for a broaching process so that it has sufficient stiffness both in the directions parallel and perpendicular to the broaching direction. Fatigue tests were carried out on a resonant machine, that allowed to detect the crack nucleation by monitoring the test frequency.